Effect of Intrinsic and Extrinsic Motivation on Academic Performance of Pokhara University Students - Sah, Mukundev Prasad (Nepalese Journal of Management, 2025)
This study examines the effect of intrinsic and extrinsic motivation on academic performance of Pokhara University students’. Academic performance is the dependent variable. The selected independent variables are student motivation, academic motivation, learning approaches, personality traits, and intrinsic and extrinsic motivation. The primary source of data is used to assess the opinions of respondents regarding student motivation, academic motivation, learning approaches, personality traits, intrinsic and extrinsic motivation, and academic performance. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of intrinsic and extrinsic motivation on academic performance of Pokhara University students. The study shows that student motivation is positively correlated to academic performance. It indicates that higher the level of student motivation, higher would be the academic performance. Similarly, academic motivation is positively correlated to academic performance. It indicates that higher the academic motivation, higher would be the academic performance. Moreover, the study showed a positive impact of learning approach on academic performance. It indicates that skills and behaviors that students use to engage in learning lead to increase in academic performance. Likewise, the study showed a positive impact of intrinsic and extrinsic motivation on academic performance. It indicates that higher the intrinsic and extrinsic motivation, higher would be the academic performance. Further, the study also showed a positive impact of personality traits on academic performance. It indicates that student’s patterns of thoughts, feelings, and behaviors lead to increase in academic performance.